2006
DOI: 10.1007/s10452-006-9032-8
|View full text |Cite
|
Sign up to set email alerts
|

Greening of the coasts: a review of the Perna viridis success story

Abstract: The green mussel Perna viridis has been receiving a lot of attention from workers working in the research areas of intertidal ecology, aquaculture, pollution monitoring, biofouling, zoogeography and invasion biology. P. viridis is a remarkable species in terms of its ability to reach very high biomass levels, to withstand environmental fluctuations, to concentrate a variety of organic and inorganic environmental pollutants, to colonise artificial marine habitats and to invade new geographic territories. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(89 citation statements)
references
References 98 publications
1
79
0
9
Order By: Relevance
“…Enrichment of surface euphotic water with nutrients favoured phytoplanktonic primary production, leading in consequence to a marked increase in trophic resources in the water column at that time. Hydrological variables, namely temperature, salinity and nutrition (food availability), seem to initiate the main reproductive activity of P. perna, as was also observed for P. viridis in other subtropical areas (Rajagopal et al 2006). However, the degree to which a given abiotic factor can affect gonad maturation in pernids varies considerably with species and geographical region.…”
Section: Ecophysiological Performance Of Perna Pernamentioning
confidence: 92%
See 2 more Smart Citations
“…Enrichment of surface euphotic water with nutrients favoured phytoplanktonic primary production, leading in consequence to a marked increase in trophic resources in the water column at that time. Hydrological variables, namely temperature, salinity and nutrition (food availability), seem to initiate the main reproductive activity of P. perna, as was also observed for P. viridis in other subtropical areas (Rajagopal et al 2006). However, the degree to which a given abiotic factor can affect gonad maturation in pernids varies considerably with species and geographical region.…”
Section: Ecophysiological Performance Of Perna Pernamentioning
confidence: 92%
“…However, reproductive and energy storage behaviour of the brown mussel along the Yemeni coastline is distinct from other subtropical representatives of the genus (Rajagopal et al 2006), reflecting particular ecological features of the bivalves and hydrological regime in the Gulf of Aden. The two bouts of spawning (late summer and early spring) differ considerably in relative intensity and extent of subsequent changes in soft tissue composition and body weight.…”
Section: Ecophysiological Performance Of Perna Pernamentioning
confidence: 99%
See 1 more Smart Citation
“…Bivalve growth depends on the environmental quality of the cultivation area and, due to the rapid growth rates of mussels these organisms are well suited for culture on a commercial scale in subtidal biotopes (RIVONKER et al, 1993;RAJAGOPAL et al, 2006). BAUTISTA (1989) has indicated that mussel growth is a function of a number of environmental parameters, mainly food and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Shellfish aquaculture is becoming a more important component of the world's food supply (FAO, 2016), given the high nutrient content of bivalves (Gopalakrishnan and Vijayavel, 2009). The green lipped mussel, Perna viridis, which is widely distributed throughout the IndoPacific region (Sidall, 1980), is among the most important aquaculture species in Southeast Asian countries (Rajagopal et al, 2006) with a 43% increase (~650,000 t) in production over the past two decades (FAO, 2015). A major concern for the future of this industry in Southeast Asia is the impact of coastal water degradation, as a result of multiple anthropogenic activities at both local and regional scales (Williams et al, 2016;Martinez et al, 2018;Sarà et al, 2018), which impact the viability and hence production of aquaculture species (Handisyde et al, 2006).…”
Section: Introductionmentioning
confidence: 99%